Le dichiarazioni anticipate di trattamento tra terapie e cure: Questioni legislative e regolamentazioni - Cucchetti, Stefano (La Scuola Cattolica, 2025)
The study of bio-legal reflection wants to examine the «living will» through a dialogue between the anthropological perspective on the human death and the recruitment of legal experience years of USA on this theme. After a first analysis that shows the ineffectiveness and the inappropriateness to use the tools of «living will» as statements of the individualist autonomy of the patient, or as a defense of the health professionalism against interference by family members or relatives to the sick, the author takes the positive development of these legal instruments as a means to promote dialogue and social responsibility around the dying. From here, through the comparison with Italian constitutional heritage and the ongoing debate in our country, it comes to formulate an original proposal.